In search of inexpensive charcoal: the relocation of steel mills to Amazonia; Em busca de carv\~ao vegetal barato: o deslocamento de siderúgicas para Amazônia - Maurílio de Abreu Monteiro (Novos Cadernos NAEA, 2006)
This paper analyzes the installation and operation process of merchant pig iron producers in Eastern Brazilian Amazonia over the past two decades. Even though fewer in number and established at a slower pace than forecast by state planners, twelve producers have been set up within the Carajas Railroad Corridor. These companies exclusively produce merchant pig iron as a commodity, requiring high amounts of charcoal-supplied energy. This paper shows how industries that, until the 1990s, were concentrated in southeastern Brazil, relocated to Amazonia. It also shows that demand for charcoal has been consolidated as the main linkage between the steel mills and socioeconomics in the Region of Carajas. Charcoal production has resulted in many social and environmental impacts in the Amazon Region. The materialization of these impacts are: increased pressure on the Amazon Rainforest, environmentally unsound practices, and charcoal production conducted under precarious, unhealthy and poorly-paid working conditions. An example of a possible alternative scenario to this situation is continued pig iron production as it is done currently, with the incorporation of small-scale electric furnaces for steel production. The possibility of installing small melt shops in the region, however, in and of itself, will not resolve the principle socioeconomic problem involved in iron ore processing in the region, linked to the deleterious effects of charcoal production, and may even aggravate it further. – – O artigo analisa o processo de instalaç\~ao, na Amazônia Oriental brasileira, de diversos produtores independentes de ferro-gusa, nas últimas duas décadas. Mesmo em número e velocidade menores do que indicava o planejamento estatal, foram implantadas no Corredor da Estrada de Ferro Carajás doze siderúrgicas. S\~ao empresas dedicadas somente à produç\~ao desta commoditie cuja produç\~ao requer elevada quantidade de energia suprida por carv\~ao vegetal. Neste artigo, mostramos que houve deslocamento para a Amazônia de indústrias que até os anos 90 estavam concentradas exclusivamente no Sudeste brasileiro e que a demanda de carv\~ao vegetal consolidou-se como principal elo de articulaç\~ao da siderurgia com a socioeconomia da regi\~ao de Carajás. A produç\~ao de carv\~ao vegetal tem acarretado muitos impactos sociais e ambientais na regi\~ao Amazônica. Impactos que se materializam pela ampliaç\~ao da press\~ao exercida sobre a floresta amazônica, por práticas ambientalmente imprudentes e pela produç\~ao do carv\~ao vegetal sustentada por trabalho precário, mal remunerado e insalubre. Exemplo de um cenário diante do qual se desenha como alternativa é a manutenç\~ao da fabricaç\~ao de ferro gusa nos moldes atuais e a incorporaç\~ao de pequenos fornos elétricos a arco para a produç\~ao de aço. Contudo, a possível instalaç\~ao de mini-aciarias na regi\~ao, por si só, n\~ao resolve o principal problema socioambiental que envolve o beneficiamento do minério de ferro na regi\~ao, vinculado aos efeitos deletérios da produç\~ao carvoeira, podendo inclusive agravá-los.
Keywords: R11; Q56; L61; R11; Q23; 330; Amazon; Metallurgy; Regional Development; Charcoal; Pig iron